Molecular simulation of [P8883][Tf2N] ionic liquid decorated silica in 6FDA-ODA based mixed matrix membrane for enhanced CO2/CH4 separation - Mehtab Ali, Darban; Serene Lock, Sow Mun; Suhaib Umer, Ilyas; Kang, Dun Yen; Mohd Hafiz Dzarfan, Othman; Yiin, Chung Loong; Sharjeel, Waqas; Zunara, Bashir (Royal Society of Chemistry, 2024)
Mixed-matrix membranes (MMMs) have been reported to have considerable scope in gas separation applications because of their merged inherent strength of a durable polymer matrix and the exceptional performance capabilities of inorganic fillers. The selection of comparatively suitable polymers with fillers that can match each other and boost interfacial compatibility while ensuring uniform dispersion of filler within the polymer is still intensively demanding and is challenging at the experimental scale. Ionic liquids (ILs) are effective in promoting better dispersion and compatibility, leading to improved separation performance. A computational molecular simulation approach is employed in current work to design a hybrid membrane having Trioctapropyl phosphonium bis(trifluoromethylsulfonyl)imide [P8883][Tf2N] IL decorated silica as a filler and 4,4′-(hexafluoroisopropylidene)diphthalic anhydride-4,4′-oxydianiline (6FDA-ODA) polymer for carbon dioxide (CO2) separation from methane (CH4). Thermophysical and gas transport properties under pure and mixed gas condition (30, 50, and 70% CO2/CH4) within the MMMs with varying filler loadings (5, 10, and 15 wt% IL-silica) are examined via Grand Canonical Monte Carlo (GCMC) and Molecular Dynamics (MD) simulations. Membrane characteristics like glass transition temperature (Tg), Fractional Free Volume (vf), X-Ray Diffraction (XRD), solubility, diffusivity, permeability, and selectivity for neat and IL-silica filled 6FDA-ODA are computed. The results show that the Tg of the composite membrane with 5 wt% IL-silica is found to be considerably higher (with 305 °C) than that of the pure 6FDA-ODA polymer having 298 °C. A higher Tg value highlights the effective dispersion and higher adhesion between the filler and polymer membrane. Additionally, CO2 permeability for 5 wt% IL-silica/6FDA-ODA MMM is significantly improved, measuring 319.0 barrer while maintaining a CO2/CH4 selectivity of 16.2. These values are 89% and 56% respectively, greater than the corresponding values of neat 6FDA-ODA membrane. Published data from the literature review is used to validate the findings and guarantee their reliability. The obtained results exhibited an error in the range of 0.7–9%. Hence, it is concluded from the study that molecular simulation can be used to design IL decorated silica incorporated within 6FDA-ODA matrix, which is able to boost the interfacial compatibility, with elevated CO2/CH4 selectivity and CO2 permeability.